Whole-genome analysis of a ST45-SCCmec IVa (2B)-t116 methicillin-resistant Staphylococcus aureus strain isolated from the sputum of a 5-year-old child with pneumonia - Huang, Lin; Guo, Rui; Lin, Jingxian; Li, Xiaowei; Li, Zhicong; Zhang, Limei; Li, Wenting; Xue, Rui; Zhang, Cheng; Feng, Xiaosan; Li, Xiaobin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMethicillin-resistant Staphylococcus aureus (MRSA) sequence type (ST) 45 is a major global MRSA lineage with huge strain diversity and a high clinical impact. In Hainan and Guangzhou of China, the ST45-MRSA was mainly associated with t116.MethodsThe MRSA strain SA2107 was isolated from the sputum of a 5-year-old child with pneumonia. The whole genome of SA2107 was sequence using Illumina (Novaseq 6000) and PacBio (Sequel IIe) sequencers, and the sequences were assembled using hybrid assembly. The carriage of antibiotic resistance genes, virulence genes, and mobile genetic elements were identified using bioinformatics tools. The comparative genomic analyses of MRSA strain SA2107 with other MRSA strains worldwide were performed.FindingsThe genome size of ST45-SCCmec IVa (2B)-t116 MRSA strain SA2107 was 2.9 Mb. Mobile genetic elements analysis of SA2107 revealed two plasmids (30,064-bp pSA2107-1 and 8,033-bp pSA2107-2), three prophages, two integrative and conjugative elements (ICEs), and two insertion sequences (ISs, IS431 and IS1272). The SCCmec IVa (2B) carried by SA2107 contained the class B mec gene complex (IS431-mecA-ΔmecR1-IS1272) and type 2 ccr gene complex (ccrA2 and ccrB2). Besides mecA, another beta-lactam resistance gene blaZ was found to located on six copies of bla complex (blaZ, blaR1, and blaI) on the chromosome of SA2107. Three kinds of virulence factors were detected on the chromosome of SA2107, including genes encoding toxins, exoenzyme, and immune-modulating protein. Notably, the three prophages harbored by the chromosome of SA2107 all carried virulence genes.ConclusionThus far, only three complete genomes available for ST45-SCCmec IVa (2B)-t116 strain from United States, Germany, and Australia, respectively. The strain SA2107 was the first complete genome data (CP104559) from China for ST45-SCCmec IVa (2B)-t116 MRSA.